Design Simulation of Raman Amplification Hybrid XGPON System with RZ and NRZ Data Format (Al-Mansour Journal, 2022)
Next-generation Passive Optical Networks (PONs), which are considered one of the most encouraging optical access networks, hasremarkably developed in the past few years and intended to greatly go forward in the nigh future. By this development the power requirements of NGPON will growth and make it no longer coveted. This paper presents Hybrid (WDM/ TDM) XGPON architecture, where in this optical fiber communication system a bidirectional optical fiber has been applied with downstream and upstream NRZ and RZ (0.6 and 0.8 duty cycle)Data Format transmission. Distributed Raman amplification is employed for upstream signal for improving the loss budget of XGPON system. Fiber attenuation, splice losses, and back-reflections as in realistic fiber plant have been considered for this XGPON system. These impairments effects on 1270 nm upstream Raman amplified signal XGPON system have beeninvestigated numerically.
Keywords: GPON; XGPON; Hybrid (WDM/ TDM); Raman Amplification